PENGARUH KUALITAS PELAYANAN, HARGA DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADANG GOLF SUKAJADI - Anggi Sadela; Lukmanul Hakim (EQUILIBIRIA, 2014)
This research was conducted in Padang Golf Sukajadi. The purpose of this study was to determine the effect of service quality, price and location Customer Satisfaction Padang Golf Sukajadi.This research was conducted with survey approach that consists of variable service quality, price and location (X), and Customer Satisfaction (Y). To prove the influence The Effect Service Quality, Price and Location CustomerSatisfaction, the authors collected data by distributing questionnaires as much as 87 respondents in the sample taken from Padang Golf Sukajadi customers who use the services Padang Golf Sukajadi. Results were collected through questionnaires were processed using the application program Statistical Product and Service Solutions (SPSS) version 20. The results showed that the variable quality of service (X1) individually do not have a positive and significant impact on customer satisfaction variable (Y), because tcount 1,266 ≤ of ttable 1663, the price variable (X2) individually have a positive and significant impact on the variable customer satisfaction (Y), because tcount 4,555 ≥ of ttable 1663, the variable location (X3) individually have a positive influence and signifiikan to variable satisfaction customer (Y), because tcount 1.752≥ of ttable 1,663. Quality of service, price and locations together providing positive and significant impact on customer satisfaction results of calculations for values ≥ 47.137 Fhitung Ftable by 2.08.